Differential photosynthetic responses to drought stress in peanut varieties: insights from transcriptome profiling and JIP-Test analysis - Jingyao Ren; Pei Guo; Xinhua Zhao; Xinlei Ma; Xin Ai; Jing Wang; Hongtao Zou; Haiqiu Yu (BMC Plant Biology)
Abstract Background Drought stress poses a critical constraint to plant growth by impairing photosynthetic efficiency in crops. Results Through transcriptome profiling of two peanut cultivars with contrasting drought tolerance, Fuhua18 (drought-sensitive, FH18) and Nonghua5 (drought-tolerant, NH5), we identified significant enrichment of differentially expressed genes in photosynthesis-related pathways. Notably, these genes were predominantly downregulated in FH18. Subsequent physiological analysis revealed cultivar-specific responses: Chlorophyll content decreased in FH18 but increased in NH5 after 24 h of drought treatment, accompanied by significant reductions in net photosynthetic rate (Pn) and water use efficiency (WUE) in both cultivars. The drought-induced physiological perturbations were further evidenced by elevated electrolyte leakage and activated antioxidant systems. To dissect photosynthetic apparatus dynamics, we implemented JIP-test analysis of chlorophyll fluorescence kinetics. Both cultivars exhibited substantial increases in Vj and Vi parameters at 24 h, while FH18 demonstrated a pronounced elevation in Vk during the O-J phase transition, suggesting severe impairment of the oxygen-evolving complex. Quantitative evaluation of photosynthetic performance indices revealed marked declines in PIabs and PItotal, indicating systemic damage to both PSI and PSII under drought stress. Comparative analysis identified 11 traits showing significant inter-cultivar variation, particularly in PSII reaction center parameters including PIabs, DI0/RC, RE0/RC, ABS/RC, and TR0/RC. Conclusion These findings provide mechanistic insights into cultivar-dependent photosynthetic responses to drought stress, offering potential biomarkers for breeding drought-resilient peanut varieties.